2022
DOI: 10.3390/ani12151932
|View full text |Cite
|
Sign up to set email alerts
|

Serological Detection of Marine Origin Brucella Exposure in Two Alaska Beluga Stocks

Abstract: Among emerging threats to the Arctic is the introduction, spread, or resurgence of disease. Marine brucellosis is an emerging disease concern among free-ranging cetaceans and is less well-studied than terrestrial forms. To investigate marine-origin Brucella sp. exposure in two beluga stocks in Alaska, USA, this study used serological status as well as real-time polymerase chain reaction (rtPCR) and bacterial culture. In total, 55 live-captured–released belugas were tested for Brucella exposure in Bristol Bay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Abs were detected in 59% of the white whale serum samples that were investigated in our study. This is in accordance with a recent study involving 167 white whales from Bristol Bay and the eastern Chukchi Sea, Alaska, USA, where an overall seroprevalence of 63% was found [ 63 ]. It is, therefore, not very surprising that white whales in Svalbard are exposed to Brucella spp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Abs were detected in 59% of the white whale serum samples that were investigated in our study. This is in accordance with a recent study involving 167 white whales from Bristol Bay and the eastern Chukchi Sea, Alaska, USA, where an overall seroprevalence of 63% was found [ 63 ]. It is, therefore, not very surprising that white whales in Svalbard are exposed to Brucella spp.…”
Section: Discussionsupporting
confidence: 93%
“…B. ceti has also been associated with mastitis, placentitis, endometritis, genital ulcers, abortion, and testicular abscess in cetaceans [ 41 , 94 ]. It is unknown whether white whales have pathological changes that are similar to those found in other cetacean species that are infected with Brucella spp., however a high prevalence of seropositivity (59%) combined with a low level of PCR (14%) and culture (0%) positive results in Alaskan white whales suggested widespread exposure, but a lack of clinical disease [ 63 ]. The three Brucella -isolates that have been retrieved from white whales belonged to a distinct B. pinnipedialis ST (ST25) that is normally associated with true seals and sea otters ( Enhydra lutris ) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A serological screening of white whales from Bristol Bay and the Chukchi Sea confirmed the presence of Brucella antibodies, indicating widespread exposure to the bacteria. However, the low level of rtPCR and lack of positive culture results demonstrated that clinical Brucellosis was not prevalent in Alaska [ 98 , 99 ]. Blood samples from 339 narwhal samples between 1984 and 2003 confirmed antibody presence to Brucella [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although B. ceti infection is of increasing concern among free-ranging cetaceans in most oceans across the world [ 9 , 29 , 41 ] there is limited information about isolates from Mediterranean Sea cetaceans. B. ceti was first isolated in 2009 from a striped dolphin stranded along the Spanish Catalonian coast [ 21 ].…”
Section: Introductionmentioning
confidence: 99%